(untitled) (Medical Forum Monthly, 2024)
Objective: To find the frequency of hyperglycemia in patients presenting with acute ischemic stroke without history of diabetes. Study Design: Cross sectional study Place and Duration of Study: This study was conducted at the Department of Medicine, Services Hospital, Lahore from 1st July 2017 to 31st December 2017. Materials and Methods: One hundred and seventy five non-diabetic patients with acute ischemic stroke were included. Each patients drawn blood sample and blood glucose level was measured by using glucometer at the time of presentation. Blood glucose level ≥200mg/dl was considered as hyperglycemia. Results: Out of 175, hyperglycemia was found in 52 (29.7%) cases. 90 (51.4%) patients had ischemic stroke and 85 (48.6%) had hemorrhagic stroke. Out of 95 hemorrhagic stroke, 32 (33.7%) had hyperglycemia and out of 80 ischemic stroke 20 (25%) was also hyperglycemia. Conclusion: The overall frequency of hyperglycemia is found to be high in stroke patients, although they did not had history of diabetes. Thus we cannot neglect the stroke patients for their blood glucose level, although they are negative for diabetes.